1999
DOI: 10.1101/gad.13.6.740
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism between RSF1 and SR proteins for both splice-site recognition in vitro and Drosophila development

Abstract: Specific recognition of splice sites within metazoan mRNA precursors (pre-mRNAs) is a potential stage for gene regulation by alternative splicing. Splicing factors of the SR protein family play a major role in this regulation, as they are required for early recognition of splice sites during spliceosome assembly. Here, we describe the characterization of RSF1, a splicing repressor isolated from Drosophila, that functionally antagonizes SR proteins. Like the latter, RSF1 comprises an amino-terminal RRM-type RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 79 publications
5
52
1
Order By: Relevance
“…Further studies will be necessary to confirm our hypothesis by performing in vitro splicing experiments (27).…”
Section: -52mentioning
confidence: 77%
“…Further studies will be necessary to confirm our hypothesis by performing in vitro splicing experiments (27).…”
Section: -52mentioning
confidence: 77%
“…65 (Zamore et al+, 1992) (Zhou & Reed, 1998), HRH1 (Ono et al+, 1994) Liu et al+, 1998Liu et al+, , 2000Cavaloc et al+, 1999;Schaal & Maniatis, 1999b)+ A surprising conclusion from these experiments is that SR proteins recognize a vast array of RNA sequences (see Table 1 (Wu & Maniatis, 1993;Amrein et al+, 1994;Kohtz et al+, 1994)+ Importantly, these protein interactions all require the RS domains of each protein (Wu & Maniatis, 1993;Amrein et al+, 1994;Kohtz et al+, 1994)+ Only recently, however, have the RS domains been shown to be sufficient to mediate protein interactions+ For instance, the RS domain of SF2/ASF has been shown to be sufficient to interact with RSF1, a Drosophila splicing repressor (Labourier et al+, 1999)+ In addition, when artificially tethered to the pre-mRNA, the RS domains of several human SR proteins are sufficient to activate enhancer-dependent splicing (Graveley & Maniatis, 1998), an activity that presumably requires protein interactions+ In contrast, the RS domain of SF2/ASF is unable to interact with U1-70K (Xiao & Manley, 1997)+ These studies indicate that the RS domains of SR pro- a N: any nucleotide; R: purine; Y: pyrimidine; S: G or C; K: U or G; W: A or U; D: A, G, or U; M: A or C+ b "SELEX" indicates that the RNA sequence was determined to be a high affinity binding site for a purified SR protein; "functional" indicates that the RNA sequence was determined to function as an SR protein-specific splicing enhancer+ teins are indeed protein interaction domains, but suggest that different protein interactions may have distinct RS domain sequence requirements+…”
Section: The Sr Protein Family Of Splicing Factorsmentioning
confidence: 99%
“…Given the prevalence of alternative splicing in higher eukaryotes (Croft et al+, 2000;International Human Genome Sequencing Consortium, 2001), it is important to understand the mechanisms that determine tissuespecific alternative splicing+ Members of the SR protein family have been shown to play an important role in regulating splice site selection, but how these proteins are themselves regulated remains unclear+ Regulated phosphorylation of SR proteins is clearly important and characterization of several kinases and phosphatases involved in SR protein modification is underway (reviewed in Gravely, 2000)+ However, the identification of proteins such as p32 (Petersen-Mahrt et al+, 1999), RSF1 (Labourier et al+, 1999), SRrp35, SRrp40 (Cowper et al+, 2001, and now SRrp86 indicates that SR proteins are subject to multiple modes of regulation, consistent with an important role in controlling splicing patterns+…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the cellular concentration of SRrp86 would be expected to alter the global activity of SR proteins, down-regulating some while up-regulating others+ Although the inhibitory activity of SRrp86 is similar to p32, RSF1, SRrp35, and SRrp40, it appears to be a broader regulator due to its ability to both activate and repress SR protein activity+ It is thought that splicing repression by RSF1 is caused by sequence-specific binding and subsequent interference with the normal protein-protein interactions of SR proteins (Labourier et al+, 1999)+ Inhibition by p32 appears to be due to repression of ASF/SF2 phosphorylation, consistent with p32 binding to only hypophosphorylated ASF/SF2 (Petersen-Mahrt et al+, 1999)+ For SRrp35 and SRrp40, it is not yet known how these proteins repress splicing but their effects are consistent with competition for RNAbinding sites (Cowper et al+, 2001)+ In contrast, SRrp86 directly interacts with target SR proteins (Barnard & Patton, 2000;J+ Li, D+C+ Barnard, & J+G+ Patton, submitted)+ It should be stressed that each of the multiple assays that have been used to examine interaction between SR proteins and SRrp86 suffer from potential pitfalls, making it difficult to quantitate the strength of interaction+ Nevertheless, regulation of SR proteins by SRrp86 appears to be distinct from simple disruption of the normal phosphorylation/dephosphorylation cycle of SR proteins, as the phosphorylation state of the target SR protein does not apparently alter interaction nor does SRrp86 appear to affect the ability of SR proteins to be phosphorylated (Barnard & Patton, 2000;D+C+ Barnard & J+G+ Patton, unpubl+)+ It is still not clear how SRrp86 is able to both activate and repress target SR proteins, but such regulation appears to be distinct from the mechanisms invoked for p32, RSF1, SRrp35, and SRrp40+ The overall picture that emerges is that a variety of mechanisms are utilized to regulate the activity of SR proteins, consistent with an important role for these proteins in controlling splice site selection+…”
Section: Regulation Of Sr Proteins By Srrp86mentioning
confidence: 99%